Pekerjaan Struktur Pusat Oleh-oleh di Bawen, Kabupaten Semarang - Konvensi Gulo; Dimas Bayu Pamungkas; Abdullah Abdullah (Jurnal Teknik Indonesia, 2021)
This study analyzes the structural work on a souvenir center construction project in Bawen, Semarang Regency. The primary focus of this research is the superstructure and foundation construction methods, material and workmanship quality control, identification of field problems, and the implemented action plan. The scope of work includes footing foundations, steel columns, steel beams, and floor slabs. The analysis includes the use of equipment, materials, and the implementation of K3. Effective coordination, selection of appropriate work methods, and consistent quality control were found to be crucial to the project's success, particularly in addressing challenges such as sloping land and K3 standards